Mechanical properties and impact energy absorption of hybrid thermoplastic nanocomposite structures - Silva, Francesco (Cranfield University, 2016)
This thesis focuses on the mechanical properties and the impact energy absorption capabilities of injection moulded hybrid three-phase polymer composites. Its main aim is to investigate the effect of different micro and nano sized filers on the mechanical properties; such as stiffness, strength, ductility, impact resistance and energy absorption capability; of short-fibre reinforced thermoplastic composites. Extensive experimental and numerical investigations were core to the research. Six different, three-phase composites, were manufactured by the integration of two types of nano-reinforcements (either nano-silica or nano-clay), or micro glass-spheres, into two types of short glass-fibre reinforced thermoplastic matrices (either Polypropylene (PP) or Polyamide (PA6)). The materials were characterized using Transmission Electron Microscopy (TEM), Wide Angle X Ray Diffraction (WAXD) and optical microscopy. The effect of matrix and reinforcement material on the mechanical properties and the energy absorption capabilities of polymer composites were studied in detail. The results are compared with the properties of standard two-phase glass-fibre reinforced polymer composites. Initial experiments focused on quasi-static uniaxial tensile and compression tests, as well as quasi-static crash tests of the conical structures. Subsequently, dynamic drop weight impact crash tests of the conical structures were conducted to investigate the influence of the nano reinforcement on the energy absorption capabilities of the polymer composites. To study propagation of the dynamic cracks and the energy absorbing mechanism, the impact event was recorded using a high-speed camera. The fracture surface was investigated with scanning electron microscopy (SEM). Furthermore, improved simulation tools were developed to accurately and effectively model nanocomposite structures subjected to dynamic loads. A constitutive model with orthotropic yield, strain rate sensitivity and strain energy density based failure criterion, was developed and implemented into Ls Dyna Finite Element (FE) code. The results show that by changing the filler and the matrix material, it is possible to control the mechanical properties and the energy absorption capability of the glass-fibre reinforced polymer nanocomposites. An increase in the mechanical properties (stiffness, strength or ductility) of PA6 composites was observed. Furthermore, nano-silica and glass-spheres reinforcements were found to improve the energy absorption capabilities of PA6 composites by changing the mode of failure, whereas nano-clay reinforcement caused a decrease in that capability. Little or negative influence of the nano-fillers was observed, when combined with PP based composites. The experimental findings were used to generate, calibrate and validate the user defined material model. The structural FE modelling proved that the model was capable of accurately and effectively representing the nanocomposite structures subjected to static and dynamic loads. Furthermore, it provided a valuable input for better understanding of the structural failure mechanism, observed in the three-phase nanocomposite structures.